Visual communication : images with messages - Lester, Paul Martin. 4 0 16; 5 (Australia : Wadsworth, Cengage Learning, 2014)
Visual communication is just as important as verbal communication, if not more important. VISUAL COMMUNICATION: IMAGES WITH MESSAGES shows you how visual perception is used in all forms of communication, whether it's graphic design, photography, television, video, or interactive media. And because it's packed with study and review tools, this communications textbook not only clearly explains the theories you need to know, it helps you prepare for tests and will help you succeed in the class.
Includes index.
Keywords: 2 -- 0; 6; Visual communication. -- 20; 20; 2